2007
DOI: 10.1111/j.1439-0272.2007.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacille Calmette-Guérin intravesical instillation and erectile function: is there a concern?

Abstract: The aim of our study was to evaluate the effect of bacille Calmette-Guérin (BCG) therapy on erectile function in a cohort of male patients affected by non-muscle invasive bladder cancer. Thirty male patients undergoing BCG treatment for non-muscle invasive bladder cancer were enrolled in the study. Their mean age was 60.4 years. None of the patients had risk factors for erectile dysfunction (ED). All subjects underwent a BCG standard schedule therapy (once weekly instillation for 6 weeks). International Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Our results should help clinicians to better inform patients of possible benefits and side effects of treatments. Previous publications on NMIBC included 4 crosssectional studies [5,11,13,14], 2 clinical trials evaluating intravesical BCG [17,18], and 3 observational prospective studies [12,15,16]. Of the latter 3, only 2 had pretreatment and posttreatment evaluations [12,16], and none of them used bladder cancer-specific HRQL instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results should help clinicians to better inform patients of possible benefits and side effects of treatments. Previous publications on NMIBC included 4 crosssectional studies [5,11,13,14], 2 clinical trials evaluating intravesical BCG [17,18], and 3 observational prospective studies [12,15,16]. Of the latter 3, only 2 had pretreatment and posttreatment evaluations [12,16], and none of them used bladder cancer-specific HRQL instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are only a few published studies regarding HRQL in patients with nonmuscle-invasive bladder cancer (NMIBC) [5,[11][12][13][14][15][16][17][18] although patients are mostly diagnosed at this stage of the disease. Taking into account the current evidence gaps regarding HRQL of patients with bladder cancer and its high incidence rates in Spain, we aimed to describe the evolution over time of HRQL (measured by generic and bladder cancer-specific instruments) of Spanish patients with NMIBC and to examine the clinical and treatmentrelated factors associated with HRQL changes during the first year of disease management.…”
Section: Introductionmentioning
confidence: 99%
“…There is little research on the impact of treatment for superficial cancer on sexual function in men or women. Intravesical therapy is typically followed by a week of pelvic pain [148] and sometimes temporary ED [149]. One small, cross‐sectional comparative study suggested that men and women receiving intravesical chemotherapy have similar sexual function as those receiving only cystoscopic tumor removal [150].…”
Section: Pelvic Nongynecologic Cancer In Men and Womenmentioning
confidence: 99%
“…Concomitant CIS was present in 35.6% (n=48, p=0.063) of the T1 subpopulation and was predominant in male smokers in their sixth decade of life. Nine patients (5.4%) in the NMIBC group underwent adjuvant chemotherapy (AC) in the form of GC [Gemcitabine (1000 mg/m2 I/V on day 1,8,15), Cisplatin (70mg/m2 on day 2)] for a total of 4 cycles, 28 days apart. Patients (n=3) having deranged kidney function and who deteriorated post first cycle of GC were shunted for Carboplatin instead of Cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Currently there are only a few published studies regarding HRQOL in NMIBC population and the authors of the present study contemplate to evaluate this specific point in their next series. [11][12][13][14][15][16][17][18] (MIBC)…”
Section: Introductionmentioning
confidence: 99%